2021
DOI: 10.1177/10731911211015355
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Thought Disorder Measure for the Hierarchical Taxonomy of Psychopathology

Abstract: The Hierarchical Taxonomy of Psychopathology consortium aims to develop a comprehensive self-report measure to assess psychopathology dimensionally. The current research describes the initial conceptualization, development, and item selection for the thought disorder spectrum and related constructs from other spectra. The thought disorder spectrum is defined primarily by the positive and disorganized traits and symptoms of schizophrenia-spectrum disorders. The Thought Disorder Sub-Workgroup identified and defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
0
8
1
1
Order By: Relevance
“…These results are consistent with views that consider mentalizing impairments and epistemic mistrust as defining features of the p factor and that place self-and interpersonal functioning at the core of psychopathology (Widiger et al, 2019;Wright et al, in press). In fact, whereas we found evidence for suspiciousness to be a pure marker of the p factor, it has previously been placed in the spectra of detachment , antagonism (Krueger et al, 2021;Mullins-Sweatt et al, 2022), or thought disorder (Cicero et al, 2022). Yet consistent with our results, studies using the Personality Inventory for DSM-5 (APA, 2013) have indicated that suspiciousness exhibits strong associations with a general PD factor but low domain-specificity (e.g., Somma et al, 2019;Williams et al, 2018).…”
Section: Hitop Structurecontrasting
confidence: 67%
See 2 more Smart Citations
“…These results are consistent with views that consider mentalizing impairments and epistemic mistrust as defining features of the p factor and that place self-and interpersonal functioning at the core of psychopathology (Widiger et al, 2019;Wright et al, in press). In fact, whereas we found evidence for suspiciousness to be a pure marker of the p factor, it has previously been placed in the spectra of detachment , antagonism (Krueger et al, 2021;Mullins-Sweatt et al, 2022), or thought disorder (Cicero et al, 2022). Yet consistent with our results, studies using the Personality Inventory for DSM-5 (APA, 2013) have indicated that suspiciousness exhibits strong associations with a general PD factor but low domain-specificity (e.g., Somma et al, 2019;Williams et al, 2018).…”
Section: Hitop Structurecontrasting
confidence: 67%
“…Using this approach, the meaning and validity of constructs can be better established, specific associations can be studied (i.e., beyond higher‐level psychopathology dimensions), jingle‐jangle fallacies can be better identified (Lawson & Robins, 2021), and, finally, the treatment utility of clinical assessments may be enhanced (Kamphuis et al, 2021). Currently, an omnibus measure of the HiTOP model is under development (Simms et al, 2022) with initial results being published for preliminary scales of HiTOP spectra (Cicero et al, 2022; Mullins‐Sweatt et al, 2022; Sellbom et al, 2022; Watson, Forbes, et al, 2022; Zimmermann et al, 2022). Until the instrument becomes available (and most likely beyond), researchers will need to rely on existing measures that capture psychopathology broadly and are compatible with HiTOP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has historically been the case, new nosological proposals are often followed by an attempt to assess psychopathology in a manner that conforms to the new perspective. Thus, it no surprise that members of the HiTOP consortium has formed working groups aimed at measuring psychopathology that is in line with their dimensional model (Cicero et al, 2021;Sellbom et al, in press;Simms et al, in press;Watson et al, 2021;Zimmerman et al, in press).…”
mentioning
confidence: 99%
“…This accords with a long line of research demonstrating that manic symptoms can be conceptualized as belonging to both internalizing and thought disorder spectra (keyes et al, 2013; kotov et al, 2020). Correspondingly, across samples, an extremely strong relationship is routinely observed between bipolar disorder and psychotic disorders due to overlapping features, such as positive symptoms, hyperactive cognition, and disrupted sleep patterns (Cicero et al, 2022;Goldberg et al, 2009). By contrast, members of the pure Internalizing class were somewhat less likely to have a psychotic or personality disorder comorbidity, but more likely to have co-occurring anxiety or PTSDs.…”
Section: : Class Membership By Mental Health Treatment Historymentioning
confidence: 99%